Neoelmis guarani Shepard & Barr, a sexually dimorphic new species from Paraguay (Insecta: Coleoptera: Elmidae: Elminae) - Shepard, William D.; Barr, Cheryl B. (Zootaxa, 2016)
Neoelmis guarani new species is described and illustrated from specimens collected in streams of the Cordillera de los Altos, southeast of Asunción and near the towns of Piribebuy and Chololó, Paraguay. Males and females of this species exhibit strong secondary sexual dimorphism not found in other known species of Neoelmis. Males have striking modifications of the pro- and mesothoracic legs and bear a pair of ventrally projecting processes on both the mesoventrite and the second abdominal ventrite. Females have the elytra modified with a pair of dorsal projections.